Alkali-Catalyzed Palm Oil Transesterification at Room Temperature : Effect of Stirring Time and Reaction Time - Jimmy, Jimmy; Setyawan, Eko Yohanes; Rastini, Endah Kusuma (Universitas Tribhuwana Tunggadewi Malang, 2022)
Transesterification of vegetable oil and methanol using a homogeneous base catalyst at a temperature of 60 ° C for 1 hour is the most efficient industrial scale. This study aims to compare the characteristics of KOH and NaOH catalysts in the transesterification of palm oil with variations in stirring time and reaction time for biodiesel production produced at room temperature. This study uses the raw material for palm oil and methanol with the ratio of mol 1: 6, variations of 1.0% catalyst and 0.5% NaOH of the weight of oil weight, 2-8 minutes stirring time variations, and 1-4 hours reaction time variations. Transesterification reactions are carried out in a closed Erlenmeyer with stirring time depending on the variation. A sampling of 10 ml is done every hour for 4 hours of reaction. Stirring is repeated with duration according to variations until the reaction time is 4 hours. Sample analysis uses Thin Layer Chromatography (TLC). The results are that (1) transesterification using a KOH catalyst gave the best results of 98.5% FAME with 8 minutes stirring time for 2 hours reaction time; (2) the NaOH catalyst gave the best result of 91.2% FAME with 8 minutes stirring time for 4 hours reaction time; (3) the KOH catalyst produced higher FAME concentrations with the same stirring time (8 minutes) in 2 hours reaction time, shorter than the NaOH catalyst, (4) transesterification with room temperature might be applied in the biodiesel industry.ABSTRAKTransesterifikasi minyak nabati dan metanol menggunakan katalis basa homogen pada temperatur 60°C selama 1 jam adalah yang paling efisien dalam skala industri. Penelitian ini bertujuan untuk membandingkan karakteristik katalis KOH dan NaOH dalam transesterifikasi minyak kelapa sawit dengan variasi waktu pengadukan dan waktu reaksi terhadap produksi biodiesel yang dihasilkan pada temperatur kamar. Penelitian ini menggunakan bahan baku minyak kelapa sawit dan metanol dengan rasio mol 1:6, variasi katalis KOH 1,0% dan NaOH 0,5% berat terhadap berat minyak, variasi waktu pengadukan 2-8 menit dan variasi waktu reaksi 1-4 jam. Reaksi transesterifikasi dilakukan secara batch dalam Erlenmeyer tertutup dengan waktu pengadukan sesuai variasi. Pengambilan sampel sebanyak 10 mL dilakukan setiap jam selama 4 jam reaksi. Pengadukan diulang dengan durasi sesuai variasi hingga waktu reaksi 4 jam. Analisis sampel menggunakan Thin Layer Chromatography (TLC). Dari penelitian ini didapatkan hasil (1) Katalis KOH memberikan hasil terbaik 98,5% volume FAME dengan waktu pengadukan 8 menit selama 2 jam waktu reaksi; (2) katalis NaOH memberikan hasil terbaik 91,2% volume FAME dengan waktu pengadukan 8 menit selama 4 jam waktu reaksi; (3) katalis KOH menghasilkan produk dengan konsentrasi FAME lebih tinggi dengan waktu pengadukan yang sama (8 menit) dalam waktu reaksi 2 jam lebih singkat dibandingkan katalis NaOH, (4) transesterifikasi menggunakan temperatur kamar memungkinkan untuk diterapkan dalam industri biodiesel.